Health belief model-based analysis of Prolanis Exercise - Cahyarani, Astika; Murdiyanto, Joko; Latifa, Annisa; Dyatmiko, Hendrian; Sekarlangit, Sekarlangit; Husmarini, Novi; Salsabila, Huda; Illahi, Annisasufitri Bryan; Rasyid, Rico Firman (Universitas 'Aisyiyah Yogyakarta, 2025)
Managing non-communicable diseases, particularly diabetes and hypertension, requires a blend of pharmacological and non-pharmacological interventions, including enhanced physical activity. The Prolanis exercise program, created by BPJS, is a promotive-preventive initiative aimed at fostering healthy lifestyle modifications through consistent physical activity and health education. The Poltekkes Kemenkes Yogyakarta Primary Clinic has implemented this program for individuals with hypertension and diabetes; however, the participation rate requires enhancement. This study seeks to examine the determinants affecting participant engagement in Prolanis Exercise through the Health Belief Model (HBM) framework. This research is a cross-sectional qualitative research with a sample of 40 participants which was then analyzed using the linear regression method. Results show that most HBM constructsperceived susceptibility, severity, benefits, barriers, and cues to actiondo not significantly influence participation. Only self-efficacy demonstrated a positive but marginally significant effect while the promotive-preventive approach showed a significant negative relationship with participation. The research results indicate that the majority of HBM constructs such as perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and cues to action do not have a significant relationship with the level of participation in the Prolanis exercise activities at the clinic. However, there are serious drawbacks to the existing promotive-preventive strategy, which highlights the need to enhance health communication approaches to be more participative, interactive, and in line with patients' needs and sociocultural context. This study highlights the importance of redesigning promotive-preventive strategies toward more participatory, context-sensitive, and empowerment-oriented health communication models, providing valuable insights for policymakers and primary healthcare providers in developing more effective community-based interventions for non-communicable disease management.